Lay Definitions of Cultural Appropriation in U.S. Community and College Student Samples - Katzarska-Miller, Iva; Faucher, Ford; Kramer, Lilly; Reysen, Stephen (Advances in Social Sciences Research Journal, 2021)
In three studies we examined lay definitions of cultural appropriation in U.S. community and college student samples. In a fourth study we examined correlates of perceptions of cultural appropriation. Using community and undergraduate student samples (Studies 1-2), and popular media articles (Study 3) we examined definitions of cultural appropriation following Rogers’ (2006) typology of cultural exchange, dominance, and subordination. The results across three studies revealed that cultural appropriation was defined predominantly as cultural exploitation. In Study 4 we examined political correctness (emotion and activism), social justice, empathy (perspective taking and empathic concern), and political orientation as correlates of cultural appropriation perceptions. Using canonical correlations, we found that cultural exploitation was the primary contributor to the synthetic predictor, and political orientation, emotion political correctness, activism political correctness, and social justice made significant contributions to the criterion variable, but not empathy. Implication and further research directions are discussed.